Interplay among physical characteristics position of play and shooting accuracy of elite female basketball players - Dominic, O. O. L.; Chado, M. A.; Gwan, J. A. (Journal of Human Sport & Exercise, 2018)
Background: Physical characteristics is often considered to exert profound influence on playing position and shooting ability in basketball. The study examined interplay of physical characteristics, playing position and shooting accuracy among elite female basketball players in Nigeria.Methodology: Population comprised all members of Zenith Bank Professional Basketball Club Champions. Based on coaches rating, the first 15players were sampled but only 14 completed the measurements. The research design was descriptive correlation. Players´ bio-data were collected using a Proforma, height and weight were measured while BMI was calculated. Research protocol included warm up and trials of 10 shots from three familiar distances. During data collection, participants were video recorded taking 30 shots in three blocks of 10 shots for each of shooting distance. Descriptive statistics; mean, standard deviation and standard error were used for data description while PPMC and ANOVA were conducted to establish statistical significance at p <= 0.05. Findings: The players had high shooting accuracy but no significant correlation with height, weight and BMI r = .030, -.181, -.041; p = 0.497. Playing positions had no significant influence on shooting accuracy F2.74m (2, 11) = 1.085, p = .372; F4.67m (2, 11) = 0.535, p = .600; F6.40m (2, 11) = 0.884, p = .441. Conclusion: Shooting accuracy is not determined by only physical characteristics and playing position. Therefore, we recommend that height, weight, and shooting performance at three distance zones should be considered for training, talent hunting and team selection.